Utilizing visitor simulations in exhibition design process: Evaluating designers' perspectives. Issue 6 (2nd November 2022) - Güler, Kutay
ABSTRACT: Throughout the design development process, simulations provide the ability to aid the designer in exploring the relationship between different variables, in various configurations, for as many iterations as needed without any physical commitment. The goal of this qualitative research is presenting in-depth perspectives of practicing design professionals on opportunities and challenges of utilising simulations in exhibition design process. Data were collected via a series of focus group interviews, adhering to a semi-structured framework. The persisting shortcomings and emerging benefits of simulations were identified and interpreted in relation to existing research. Notable findings indicated a significant demand towards a clear and intuitive user interface and visual output, stressed the minimal presence in work and educational environments and the resulting lack of synergy, and lastly, in addition to the skill requirements and steep learning curve, underlined the reliance on specialised experience to interpret and compensate the output.